(untitled) (SCHOOLAR: Social and Literature Study in Education, 2022)
Learning development Strategi is a learning plan or objective,in order to be achieved optimally.The history of Islamic culture is a past event that was born by Muslims in line with the revelation from Allah SWT. Student learning achievement is an outcome that has been achieved as a change of behavior passed by experience and insight to be able to interact with the environment that concerns the cognitive, affective and psychomotor realms that have been stated in the final result / raport. The impact is on Classical subjects so lack of interest to learn. The purpose of this research is to know the strategy of ski learning development in improving student achievement in MTs Salafiyah Syafiiyah Tebuireng Jombang.The method used is qualitative method. Data collection conducted is interviewing informants in MTs Salafiyah Syafiiyah Tebuireng Jombang.The results showed that the model used teacher learning, studen active learning and demontrasi. While the learning strategy is improving the ability to think, it-based learning, lectures using props.model and strategy can be used because it is considered the most efficient to be used in ski learning.